(3cJGH efgGL GdHjGf ajeG jSJYedg GdEfSGfs - (3jMji Hf YjSi Hf LRdI GdHZOGOj, CHh Ydj,J (B493 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HOjY eUfhYGJg SejJg HefgGL GdHjGf ajeG jSJYedg GdCfSGf aVefJg PcQ LejY GdCOhjI hGdCTQHI hGdCZPjI s
(3BNQgG (B:s
(3gh MGQ jGHS Sgd GdHdZe hbO GSJhai PcQg hTQMg hddg GdMeO Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B161 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B218s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1870s
Keywords: (3GdWHs